Negotiating Gender Roles: The Shift of Wives Role as the Main Breadwinners in Wijirejo Village, Indonesia (Program Studi Hukum Keluarga Islam, 2025)
This study aims to analyze the transformation of wives’ economic roles as primary breadwinners in Muslim families in Wijirejo Village, Indonesia, and to examine its normative legitimacy through the perspectives of maṣlaḥah and Robert K. Merton’s structural-functionalism theory. The study addresses the tension between the normative construction of Islamic family law, which positions the husband as qawwām with primary financial responsibility, and the social reality in which wives increasingly assume the role of main breadwinners due to economic pressures and unstable husbands’ incomes. Employing a qualitative sociological approach, data were collected through in-depth interviews with 12 wives who serve as primary breadwinners, participatory observation, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings indicate that this role shift represents a form of structural and social adaptation grounded in the principle of maṣlaḥah. The wife’s role as the main breadwinner does not contradict the Maqāṣid al-Sharī‘ah as long as it generates benefits and prevents harm. Integrating maṣlaḥah with Merton’s functionalism reveals how Muslim families maintain social balance and religious values amid economic change. This study contributes to Islamic family law scholarship by offering an integrative socio-normative perspective on gender roles in contemporary Muslim society.